2002
DOI: 10.1046/j.1365-2648.2002.02323.x
|View full text |Cite
|
Sign up to set email alerts
|

Dis/integrated care: family caregivers and in‐hospital respite care

Abstract: Nurses' practices in this study were a critical element in facilitating, or alternately constraining, family caregivers' ability to relinquish care and to take full advantage of the respite time. The research findings highlight the need for nurses and other formal caregivers to locate themselves in a secondary and supporting caregiving role, to acknowledge the family caregivers as the primary caregiver, and use family caregivers in-depth and intimate knowledge of the needs of their relative to inform care with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
90
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(91 citation statements)
references
References 22 publications
1
90
0
Order By: Relevance
“…This is contradictory to a literature review which found no evidence of deterioration of the elderly during respite care (10). Nevertheless, some other studies have shown functional decline of elderly during ORC, for example in Canada and New Zealand, deterioration of the elderly during respite care was an important reason why many carers did not take advantage of the respite time (21,27). One reason for our findings can be that the elderly were more frail than the care receivers in other studies as they were assessed to need NH care.…”
Section: Functional Decline Of the Elderly During Orcmentioning
confidence: 91%
See 1 more Smart Citation
“…This is contradictory to a literature review which found no evidence of deterioration of the elderly during respite care (10). Nevertheless, some other studies have shown functional decline of elderly during ORC, for example in Canada and New Zealand, deterioration of the elderly during respite care was an important reason why many carers did not take advantage of the respite time (21,27). One reason for our findings can be that the elderly were more frail than the care receivers in other studies as they were assessed to need NH care.…”
Section: Functional Decline Of the Elderly During Orcmentioning
confidence: 91%
“…They were in great need of individually adjusted support to be able to continue their caregiving (4). In response to carers' need, respite care has been developed (5) to support carers by offering them temporary relief and assisting them in maintaining their relative at home (6). The purpose of overnight respite care (ORC) is twofold: to give the elderly more extensive care and/or training than possible at home, and to give carers temporary relief.…”
Section: Introductionmentioning
confidence: 99%
“…Gilmour 171 The perception of the quality of service provision is central to a carer's decision to take up respite care, and impacts on many of the other issues discussed here. Even if respite use continues in the face of a perceived lack of quality the carer may not achieve an effective respite experience, as one carer in the Strang 205 study clearly states:…”
Section: Quality Of Carementioning
confidence: 99%
“…Furthermore, extra care was required at home to help the person regain their previous level of health. Gilmour 171 Being away from the one-to-one care given by the informal carer could also lead to loss of continence, which is a significant factor in the ability of carers to maintain the care recipient in the home environment. Other more serious health impacts included reports of a hip fracture resulting from a fall that went unnoticed and the need to admit one man to hospital because of a blocked catheter.…”
mentioning
confidence: 99%
See 1 more Smart Citation